(untitled) (Singaporean Journal of Business Economics and Management, 2017)
This paper aims to specify the model of human resource development based on organizational culture in Ministry of Justice in Iran. The study was used mixed methods research. Also, there were two populations. One population included the experts for qualitative analysis and the other population was all people in the organization for quantitative analysis. The 13 selective codes and 59 open codes were classified after the interview with experts. Next, 13 hypotheses were defined based on the selective codes of the model. Finally, testing of hypotheses confirmed all of them and the variables of the model were determined.